Exopolysaccharides from Rhizopus Nigricans Inhibit Proliferation and Induce Apoptosis in Human Lung Adenocarcinoma A549 Cells - Li, Mengmeng; Wu, Jinhui; Ni, Xiuwen; Liu, Chunyan; Xu, Jun; Wang, Hongyun; Li, Zhang (Journal of Contemporary Medical Sciences, 2025)
Objective: To analyse the effects of an exopolysaccharide (EPS2-1) obtained from the fermentation broth of Rhizopus nigricans on the viability and apoptosis of human lung adenocarcinoma (A549) cells. Methods: Lung cancer cells were cultured in vitro and divided into the control and exopolysaccharide-treated groups. CCK-8 and colony formation assays were performed to measure the proliferation of A549 cells. Caspase activity was measured using a colorimetric assay. The apoptosis rate, reactive oxygen species (ROS) production, and mitochondrial membrane potential (MMP) were evaluated using flow cytometry. Results: EPS2-1 effectively suppressed A549 cell proliferation (p < 0.05). At the same time, EPS2-1 significantly increased the enzyme activity of caspase-8 and caspase-3 compared with that in the control group (p < 0.05) and facilitated the apoptosis of A549 cells. Furthermore, EPS2-1 increased the accumulation of intracellular ROS and induced a reduction in MMP in A549 cells. These findings suggest that EPS2-1 initiated apoptosis in A549 cells via the mitochondrial pathway. Conclusion: EPS2-1 significantly inhibited A549 cell proliferation and induced apoptosis via ROS accumulation and mitochondrial dysfunction, suggesting its potential as an anti-cancer agent. This study provides the first evidence that Rhizopus nigricans-derived polysaccharides exhibit induce-apoptosis activity on A549 cells through ROS-mediated mitochondrial dysfunction, establishing a novel pharmacological foundation for fungal polysaccharide research and development of natural antitumor agents.